Aortic atresia: survival to adulthood without surgery. Issue 5 (November 1990) - Maxwell, P; Somerville, J
Abstract : Aortic atresia is a rare congenital cardiac defect. It usually leads to death in the neonatal period. A patient with aortic atresia has survived to the age of 24 years without any surgical procedure. In view of the uncertain results of reconstructive surgery this case may have therapeutic implications.